The Effect of Income on Teachers' Work Discipline at MTS in All Districts Bolaang Mongondow Selatan - Berlian Hala'a; Melizubaida Mahmud; Sudirman Sudirman; Meyko Panigoro; Abdulrahim Maruwae (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aimed to determine how much income affects teacher work discipline in all MTS throughout south Bolaang Mongondow, A quantitative approach was adopted, utilizing a descriptive quantitative method with a sample size of 38 teachers. Data collection techniques included observation, questionnaires, and documentation. Data analysis was performed using simple regression analysis. The study's results reveal a positive and significant relationship between income and teacher work discipline in all MTS throughout South Bolaang Mongondow. The coefficient of determination obtained from the regression model is 0,587, indicating that 58.7% of the variability in work discipline is explained by income. In other words, higher income correlates with iproved work discipline among teachers. Meanwhile, 41.3% of the variation in teacher word discipline is attributed to other factors not examined in this study.